Pengaruh Kebijakan Treatment Karyawan Terhadap Efektivitas Pengendalian Internal dan Kualitas Laporan Keuangan Sektor Publik Kabupaten Situbondo - Lita Permata Sari; Ediyanto Ediyanto (Growth, 2018)
This study aimed to get empirical evidence about the effect of treatment policy of employees on the effectiveness of internal controls and the quality of public sector financial statements.These samples included 102 respondents who work and have a position as an officer of the financial administration and assets as well as treasurer of the regional work units (SKPD) Government of Situbondo District.The sampling technique used purposive sampling, that is choosing the sample with a sample of criteria that the sample involved at least 2 years experience in financial reporting in each SKPD.Methods of data collection is performed by questionnaires distributed directly. Data analysis using Path Analysis with software SPSS version 20. This study provided empirical evidence that the treatment policy of employees has positive effect on the effectiveness of internal controls. Instead, the treatment policy of employees has no effect on the quality of public sector financial statements.Moreover, empirical evidence show that the effect of treatment policy of employees on the quality of financial statements is mediated by the effectiveness of internal controls. It meanings that through the effectiveness of internal controls, the treatment policy of employees can indirectly effecton the quality of financial statements.